13 In-hospital STEMI mortality: repatriation can lead to invalid conclusions. (October 2018) - Kinsley, T; Fahy, EF; Casserly, I; Mahon, N; Doyle, B; Keelan, P; O'Neill, J; Keelan, T; Galvin, J; Kennedy, M; McCann, H; Blake, GJ
Abstract : Introduction: Patients who undergo PPCI in MMUH for STEMI are routinely immediately repatriated to their local hospital, assuming clinical stability. We sought to analyse in hospital mortality rates in the MMUH patients who were not immediately repatriated due to clinical instability and compare this with all STEMI patients from the MMUH catchment area. Methods: We performed retrospective analysis on all STEMI cases with PPCI in MMUH from July 2017 until January 2018. Patients were grouped into repatriated and non-repatriated patients. Within the non-repatriated group, patients were further divided into patients who either fell within MMUH catchment area or patients who were clinically too unstable for immediate repatriation. Analysis was performed by direct review of the medical notes for each patient, to ascertain the clinical reasons for not repatriating patients immediately, and to determine survival to discharge. Results: There were 209 cases of PPCI for STEMI in MMUH for this six month period. Of these, 36 were from the MMUH catchment (17%). Of the remaining 173 patients eligible for repatriation, 28 (16%) were admitted to the MMUH and not repatriated due to clinical instability. A comparison of clinical characteristics between the MMUH catchment group (36) and the Non-repatriated group (28) respectively (table 1): Arrhythmia 6 v 11 (17% v 39%), Cardiogenic Shock 8 v 16 (22% v 57%), Mechanical Ventilation 4 v 7 (11% v 25%), IABP 2 v 5 (5% v 18%), Mechanical complications 0 v 1 (0% v 3.5%), Vascular access complications 0 v 2 (0% v 7%), Stroke 3 v 3 (8.5% v 11%), OHCA 4 v 3 (11.4% v 10%).In hospital mortality for STEMI patients from MMUH catchment area was 8.3% (3/36). In hospital mortality for non-repatriated patients was significantly higher 21.4% (6/28) (table 2). Overall in hospital mortality for all patients admitted to the MMUH was 14% (9/64). Conclusions: At our PPCI centre overall STEMI in hospital mortality rates are increased by a cohort of patients who are more clinically unstable than the majority of STEMI patients. Crude comparison of in-hospital mortality rates can be misleading, particularly with an active repatriation STEMI program.